PEMPROGRAMAN MESIN BOR OTOMATIS BERBASIS ATMEGA 328 YANG TERINTEGRASI LCD TOUCHSCREEN NEXTION 3,2 INCHI - Ikbal, Muhammad Nur; Gunadi, Isnain (BERKALA FISIKA, 2019)
The aim of this study is to develop an automatic drilling machine based on Atmega328integrated with the 3.2 inch-Nextion LCD Touchscreen. The drilling machine was designed to automatically determine the distance and the number of holes according to the LCD touchscreen nextion display, both for movement on the Y-axis and X-axis, using a PH268-21 series unipolar of stepper motor and was controlled by a CSD2120P type motor driver. Meanwhile, to perforate the workpiece using an AC motor with a voltage of 220 volts. Machine control used 2 Limit Switches as calculation indicators to be processed by a microcontroller that has been programmed using the Arduino IDE software and displayed on the Nextion LCD touchscreen. From the test it was found that this automation system is very accurate to produce number of holes. The accuracy of distance used as an initial indicator of this automatic drilling machine was 1 mm and it can be changed according to desired needs. Therefore, this automatic drilling machine can provide more effective and efficient results so that it is expected to help in maximizing results for industrial-scale.Keywords: limit switch, unipolar stepper motor, micro-controller, Nextion LCD touchscreen